Pengaruh Pendidikan, Keterampilan, Pengalaman Kerja, dan Komitmen Organisasi Terhadap Kinerja Pegawai Outsourcing Pada Pusat Pemanduan Lalu Lintas Penerbangan Makassar Pada PT. Angkasa Pura I - Hasiah Hasiah; Fauziah Fauziah (STIM-LPI Makassar, 2021)
This research is to determine the influence of education, skills, work experience and organizational commitment on the performance of Outsourcing employees at the Makassar Air Traffic Control Center at PT. Angkasa Pura I, using multiple regression analysis where simultaneously the factors of education, skills, experience and organizational commitment have a positive and significant effect on the performance of Outsourcing employees Air Traffic Control Center at PT. Angkasa Pura I and the results of partial analysis with multiple linear regression analysis show that the experience factor is the variable that has the greatest contribution to improving the performance of Outsourcing employees at the Air Traffic Control Center at PT. Angkasa Pura I.